A novel tool for the assessment of sport climbers` movement performance - Taylor, N.; Giles, D.; Panácková, M.; Mitchell, J.; Chidley, J.; Draper, N. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To assess the validity and reliability of a novel movement-performance assessment tool for climbing/sport climbing. Methods: First, salient climbing movement-performance factors were identified through an iterative consultation process with 10 expert climbing coaches; the resulting Climber`s Movement Performance Assessment Tool (CM-PAT) contained 14 items in 5 categories. Second, 61 intermediate to advanced climbers ascended a single route, which was video recorded. Subsequently, 4 experienced (>10 y coaching) coaches used the CM-PAT to observe and score the climbers` performance. Interrater reliability and comparisons with existing measures of climbing performance (6-mo self-reported ability, success and failure, climbing pace [m/min], and geometric entropy) were made. Results: Intraclass correlation coefficient (2,k) for the 4 raters demonstrated excellent reliability (>.81) between observers and good to excellent test-retest reliability (.71-.91). Pearson correlations between self-reported ability and CM-PAT scores explained 61% of the variance in self-reported climbing performance compared with 16% for geometric entropy and 52% for climbing pace. Considering differences in successful and unsuccessful climbers, the CM-PAT (P<.0005; d=2.14), geometric entropy (P=.014; d=0.67), and pace (P<.0005; d=1.88) were able to differentiate between groups. Conclusions: The CM-PAT is the first sport climbing performance observational instrument to be developed through a thorough iterative process with expert coaches. Excellent interrater and test-retest reliability and excellent agreement with self-reported ability and with existing quantitative measures of performance support its recommendation for use in coaching and research contexts. Notably, a key advantage over existing measures is the identification of coachable elements of performance.